Basal cell carcinoma arising in a tattoo - Nicole Edmonds; Thomas Cropley; Mary M Noland; Richard Hal Flowers (Wolters Kluwer Medknow Publications, 2020)
Cutaneous malignancies may uncommonly arise in the setting of injury to the skin from a variety of etiologies. While melanoma, squamous cell carcinoma, and basal cell carcinoma (BCC) have all been reported at tattoo sites, BCC is the least common, with the present case being only the 12th such case reported in the literature. We present a case of a large BCC of 15 years duration arising within a blue/black tattoo on the patient's left upper arm. The patient was treated with 6 weeks of imiquimod cream with promising results and started a second 6-week regimen to clear residual tumor. Of the 12 reported cases of BCC arising within tattoo sites, the majority of patients have been male (7/12 patients) and the majority of the BCCs developed within the blue or black pigment of the tattoo (8/12 patients) on sun-exposed skin (9/12 patients). The average age at the diagnosis is 53.5 years, and the average duration between tattoo placement and BCC onset is 18.3 years. It has been hypothesized that tattoo ink may be related to the development of malignancies as either a primary carcinogen or cocarcinogen with ultraviolet exposure. Nevertheless, the link between tattoo ink and malignancy may also be coincidental considering the number of tattooed individuals worldwide and the extreme rarity of BCCs that have developed in tattoos. Our purpose is to raise the awareness of the development of cutaneous malignancies within tattoo sites and encourage the physicians to include cutaneous malignancy in the differential diagnosis of "rash" arising in a tattoo.